T Follicular Regulatory Cell Suppression of T Follicular Helper Cell Function Is Context-Dependent in vitro - Lopez-Ocasio, Maria; Buszko, Maja; Blain, Melissa; Wang, Ke; Shevach, Ethan M. (Frontiers in Immunology, 2020)
The production of antibody-secreting plasma cells and memory B cells requires the interaction of T follicular helper (Tfh) cells with B cells in the follicle and is modulated by T follicular regulatory (Tfr) cells. We compare the effects of Tfr cells in an in vitro model of bystander Tfh function in the absence of BCR engagement and in a model in which mimics cognate T-B interactions in which the BCR is engaged. In the absence of Tfr cells, Tfh cells from primed mice induce naive B cell differentiation into GC B cells and class switch recombination (CSR) in the presence of anti-CD3 alone or anti-CD3/IgM in a contact-dependent manner. Addition of primed Tfr cells efficiently suppressed GC B cell proliferation, differentiation and CSR in the anti-CD3 alone cultures, but only moderately suppressed BCR-stimulated B cells. When stimulated with anti-CD3 alone, IL-4 is critical for the induction of GC B cells and CSR. IL-21 plays a minimal role in GC B cell differentiation, but a greater role in switching. When the BCR is engaged, IL-4 is primarily required for switching and IL-21 only modestly affects switching. CD40L expression was critical for Tfh-mediated B cell proliferation/differentiation in the absence of B cell engagement. When the BCR was engaged, proliferation of CD40 deficient B cells was partially restored, but was susceptible to suppression by Tfr. These studies suggest that in vitro Tfr suppressor function is complex and is modulated by BCR signaling and CD40-CD40L interactions.